The Decisions in the Teaching and the Development of Meta-Comprehensive Knowledge (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
This paper attempts to explain how school factors may influence the development of meta-comprehensive knowledge of reading.  This refers mainly to the students' knowledge about the reading task, the strategies required in this process and the text they are reading.  The main focus is on exploring how Spanish language and communications teachers' decisions may foster the development of this kind of knowledge in students. This study included nine eighth-grade courses,  selecting the one with the highest scores on meta-comprehensive knowledge and the one with the lowest scores as well.  Spanish language and communications teachers' classes were observed and then interviews were held.  The results show differences between both teachers,  related to their concept of language as a teaching object,  and the characteristics of their pedagogical actions in the classroom.
Keywords: meta-comprehensive knowledge; language teaching; pedagogical actions; classroom